PENINGKATAN PENGETAHUAN PERAWAT DAN BIDAN DALAM MENGURANGI INTENSITAS NYERI PERSALINAN - Riris Sitorus; Grace Erlyn; Diah Evawanna Anuhgera; Nikmah Jalilah Ritonga; Desideria Yosepha Ginting (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Labor pain was a problem that has not received special attention, even though the goal of intrapartum care itself was to reduce pain during labor. It was not uncommon to find that every mother giving birth were very worried about the labor process that would be passed, this can trigger the perception of maternal pain. In addition, there were also mothers who were afraid and couldn’t stand the pain of going through the labor process or opening the birth canal because they feel severe pain during the first stage of labor, this sometimes makes mothers think short and choose the Sectio Cesaria action as one of the best solutions, whereas delivery by Caesarean section has many risks and the postpartum healing process takes longer than those of a normal delivery. Based on the results of the research that has been done, it is found that the reduction of labor pain could be done by using effleurage massage. This technique was quite simple and easy to do as a pain relief for mothers during the active phase of labor. This massage was quite easy to do by health professionals such as midwives, and could also be applied by families or mothers who were in labor by giving gentle, long and continuous strokes. Nurses and midwives must have the ability to manage labor pain management for mothers with the delivery process.The aimed of this activities was to increased nurse and midwife’s knowledge in reduce the labour pain intensity.